Integrating Directed Reading Thinking Activity (DRTA) with Peer Assisted Learning Strategy (PALS) to Improve Students’ Reading Comprehension Using Narrative Text - Agnescia, Elany; Raja, Patuan; Sukirlan, Muhammad (Universitas PGRI Sumatera Barat, 2025)
This study aimed to find out whether the integrated Directed Reading Thinking Activity (DRTA) with Peer Assisted Learning Strategy (PALS) improves students' reading comprehension better than the Original DRTA. This research employed a quantitative method. The study was conducted with the first-grade students at SMA Negeri 4 Bandar Lampung. Two classes were used: an experimental class, which was taught using the integrated DRTA with PALS, and a control class, which was taught using the original DRTA. The results of the post-test showed that the control group had a mean score of 80.51, whereas the experimental group had a higher mean score of 83.94. The t-test results for the post-test indicated a Sig. (2-tailed) value was 0.049 (< 0.05), there is a statistically significant difference between the two groups after the treatment. The experimental group achieved better improvement in students’ reading comprehension compared to the control group. These findings suggest that integrated DRTA with PALS improves students' reading comprehension. Keywords: DRTA, PALS, Reading Comprehension